2021
DOI: 10.1155/2021/3371091
|View full text |Cite
|
Sign up to set email alerts
|

A Study on COMP and CTX-II as Molecular Markers for the Diagnosis of Intervertebral Disc Degeneration

Abstract: Background. Diagnosis of intervertebral disc degeneration (IVDD) is challenging at the early stage. The cartilage oligomeric matrix protein (COMP) and extracellular matrix degradation products of C-telopeptide of type II collagen (CTX-II) serve as markers for the serological diagnosis of IVDD. Oxidative stress might cause IVDD and matrix degeneration. Methods. A total of 128 male adult Sprague–Dawley (SD) rats were randomly and equally assigned to the experimental and control groups. The experimental group was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Although sCOMP levels decreased at 4 weeks, which may be attributed to degradation, it nevertheless remained higher than pre-surgical levels. Similar findings were obtained in Sprague–Dawley rats in a previous study of IVDD [ 31 ] but most importantly we were able to substantiate this etiology in patients. In humans with LBP, we found that the concentration of sCOMP was positively correlated with the Pfirrmann classification of IVD, higher sCOMP values with higher pain scores.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although sCOMP levels decreased at 4 weeks, which may be attributed to degradation, it nevertheless remained higher than pre-surgical levels. Similar findings were obtained in Sprague–Dawley rats in a previous study of IVDD [ 31 ] but most importantly we were able to substantiate this etiology in patients. In humans with LBP, we found that the concentration of sCOMP was positively correlated with the Pfirrmann classification of IVD, higher sCOMP values with higher pain scores.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in OA, RA and reactive arthritis have shown that COMP is degraded and released into serum and/or urine in the early pathogenic stages, with serum COMP (sCOMP) levels distinguishing between OA and healthy individuals and reflecting disease severity [ 27 30 ]. Moreover, recent findings in the animal model of IVDD reported that sCOMP was upregulated during the progression of IVDD [ 31 ]. These instructive findings suggest that the relationship between COMP release and the clinicopathological characteristics of IVDD needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, collagen and aggrecan turnover in ECM was observed in degenerated discs (Sivan et al, 2014;Trefilova et al, 2021). COMP, the cartilage oligomeric matrix protein, was also found as a marker of IVDD (Qi et al, 2021). Several cytokines including IL1, IL5, IL6, IL7, IL10 TLR4, and TNF-alpha were found to promote extracellular matrix degradation, leading to the degeneration of IVD (Klawitter et al, 2014;Osuka et al, 2014;Risbud and Shapiro, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…IVD specimens used to measure the LDD and LBP biomarkers would be preferable, but implausible in general population studies. However, determination of serum/plasma concentrations of several cytokines and other soluble molecules has been successfully used for monitoring the initiation, intensity, and progression of human LBP [ 3 , 14 ], and LDD [ 51 ]. These obviously could also be done with respect to GDF15 and vaspin.…”
Section: Discussionmentioning
confidence: 99%